1994
DOI: 10.1017/s0813483900004514
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Parent Training Versus Dietary Education in the Treatment of Children with Persistent Feeding Difficulties

Abstract: This controlled treatment-outcome study compared the effects of behavioural parent training (BPT) and standard dietary education (SDE) on the mealtime interaction, feeding behaviour, nutritional status, and adjustment of children with feeding disorders. Participants were 20 children (aged between 18 months and five years) with persistent feeding difficulties, and their families. Children underwent initial screening (involving medical assessment, behavioural observation of mealtime interaction, nutritional inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 28 publications
(11 reference statements)
0
24
0
2
Order By: Relevance
“…Several meta-analyses document the effectiveness of parenting programs across a range of parental and child outcomes (Barlow et al 2002;Kaminski et al 2008;Lundahl et al 2006;Serketich and Dumas 1996) such as autism (McConachie and Diggle 2007), developmental disabilities (Plant and Sanders 2007), anxiety disorders (Cartwright-Hatton et al 2011), feeding and sleeping problems (Turner et al 1994;Werle et al 1993), drug and alcohol problems (Battistich et al 2000), anti-social behavior (Scott et al 2001), attention deficit hyperactivity disorder (Hoath and Sanders 2002) and recurrent pain syndromes . Parenting programs have also been shown to improve couple interaction quality (Cowan et al 2011), parenting competence and stress (Gross et al 2003;Nixon et al 2003) and maternal depression (Sanders and McFarland 2000).…”
Section: Definition Of Parenting Programsmentioning
confidence: 99%
“…Several meta-analyses document the effectiveness of parenting programs across a range of parental and child outcomes (Barlow et al 2002;Kaminski et al 2008;Lundahl et al 2006;Serketich and Dumas 1996) such as autism (McConachie and Diggle 2007), developmental disabilities (Plant and Sanders 2007), anxiety disorders (Cartwright-Hatton et al 2011), feeding and sleeping problems (Turner et al 1994;Werle et al 1993), drug and alcohol problems (Battistich et al 2000), anti-social behavior (Scott et al 2001), attention deficit hyperactivity disorder (Hoath and Sanders 2002) and recurrent pain syndromes . Parenting programs have also been shown to improve couple interaction quality (Cowan et al 2011), parenting competence and stress (Gross et al 2003;Nixon et al 2003) and maternal depression (Sanders and McFarland 2000).…”
Section: Definition Of Parenting Programsmentioning
confidence: 99%
“…Although various behavioral techniques have been used to treat various feeding problems (Babbitt et al, 1994;Blackman & Nelson, 1985, 1987Handen, Mandell & Russo, 1986;Luiselli, 1988Luiselli, , 1993Luiselli, , 1994Luiselli & Gleason, 1987;Riordan, Iwata, Finney, Wohl, & Stanley, 1984;Turner, Sanders, & Wall, 1994;Werle, Murphy, & Budd, 1993), the technique that is believed to be most helpful to treat PTFD is flooding (Chatoor & Benoit, 1996). A brief review of the theory and techniques of behavior therapy is useful to provide a framework from which to understand why flooding may be the technique of choice to treat PTFD.…”
Section: Flooding (Implosion) As Treatment For Ptfdmentioning
confidence: 99%
“…While some studies have made clear links between age and meal length (Turner et al, 1994 1996). The current study found age to influence both observed and parent-reported meal 326 duration, thus further research should be directed towards clarifying this complex relationship 327 between the developmental stage of the child and meal length.…”
Section: Problem-eaters Versus Controls 227mentioning
confidence: 99%
“…The MOS is an established method of coding that has been shown to reliably 183 differentiate children with and without feeding difficulties (Sanders, Patel, et al, 1993) and to 184 capture post-intervention change (Turner, Sanders, & Wall, 1994). The MOS has good inter-185 rater reliability (mean k: parent codes=.83, child codes=.80; Sanders, Patel, et al, 1993 …”
mentioning
confidence: 99%